Measurement of cutaneous lymphatic flow rates in patients with skin cancer: area extraction method. Issue 6 (June 2014) - Fujiwara, Masao; Sawada, Michifumi; Kasuya, Akira; Matsushita, Yuki; Yamada, Moe; Fukamizu, Hidekazu; Magata, Yasuhiro; Tokura, Yoshiki; Sakahara, Harumi
Abstract Some recent reports have revealed that the long scintigraphic appearance time (SAT), defined as the time between radionuclide injection and first sentinel lymph node (SLN) visualization in lymphoscintigraphy, is a negative predictive parameter of nodal metastasis in patients with melanoma. However, most of the methods used to measure the SAT were ambiguous because they utilized visualization in lymphoscintigraphy. We herein introduce a novel method by which to measure the SAT and lymphatic flow rate. The data of 33 patients with primary skin cancer were used. Sequential images were obtained using dynamic lymphoscintigraphy, and a time–activity curve of the SLN was created. The time at which the counts reached plateau was newly defined as an alternative to the SAT and was termed the scintigraphic saturation time (SST). The figure obtained by division of the distance by the SST was newly defined as an alternative to the lymphatic flow rate and termed the lymphatic transit rate (LTR). The SST was clearly determined. It ranged from 220 to 1430 s (mean, 805 s). Pathological examination revealed nodal metastasis in five patients. In 28 patients without metastasis, the mean LTR was in the order of lower limbs (4.07 ± 0.35 cm/min), upper limbs (2.67 ± 0.33 cm/min), trunk (1.79 ± 0.47 cm/min), and head and neck (1.11 ± 0.22 cm/min). The LTRs were higher in patients with nodal metastasis than those without. This method may be effective for accurate measurement of the SAT and lymphatic flow rate.